Contemporary Knowledge Workers and the Boundaryless Work–Life Interface: Implications for the Human Resource Management of the Knowledge Workforce - Field, Justin Craig; Chan, Xi Wen (Frontiers in Psychology, 2018)
In the last decade, knowledge workers have seen tremendous change in ways of working and living, driven by proliferating mobile communication technologies, the rise of dual-income couples, shifting expectations of ideal motherhood and involved fatherhood, and the rise of flexible working arrangements. Drawing on 54 interviews with Australian knowledge workers in the information technology sector, we argue that the interface between work and life is now blurred and boundaryless for knowledge workers. By this, we mean that knowledge workers are empowered and enslaved by mobile devices that bring work into the home, and family into the workplace. Knowledge workers take advantage of flexible working to craft unique, personal arrangements to suit their work, family, personal and community pursuits. They choose where and when to work, often interweaving the work domain and the home–family domain multiple times per day. Teleworkers, for example, attain rapid boundary transitions rending the work–home boundary, thus making their experience of the work–life interface boundaryless.